Cashless Behavior And E-Wallets In Gen Z’s Financial Management - Djiwono, Jennifer Audreylia; Kondana, Tiffany Evelyn; Laulyta, Reyna Reng Suy; Yantho, Olivia; Suade, Yuyun Karystin Meilisa (Value : Jurnal Manajemen dan Akuntansi, 2025)
This study investigates the influence of cashless payments and digital wallets on the financial management of Generation Z in Makassar, focusing on key issues such as impulsive spending, low financial literacy, and data security. Although this generation is known to be technologically literate, many still lack the skills to manage their finances wisely. The study employed a quantitative approach with an explanatory design and involved 120 respondents aged 17 to 26 who actively use e-wallets in their daily financial activities. Data were analyzed using multiple linear regression with SPSS version 26. Statistical results showed that cashless payment behavior had a positive and significant effect on personal financial management (β = 0.421, p < 0.01), as did the use of digital wallets (β = 0.388, p < 0.01), contributing to greater efficiency and accuracy in financial management. The R² value of 0.56 indicates that both independent variables collectively explain 56% of the variance in personal financial management. Features such as automatic transaction recording, spending notifications, and payment reminders play a role in enhancing financial literacy and discipline. This study concludes that the careful adoption of digital financial technology can serve as a strategic tool for fostering healthy, structured, and sustainable financial behavior among Generation Z.